2017
DOI: 10.4172/neuropsychiatry.1000317
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychological Anomalies in Parkinsons Disease: An Insight into Non-Motor Characteristic Features

Abstract: While most of the clinical concerns for Parkinson's disease (PD) are limited to the cardinal motor abnormalities, non-motor features like cognitive and psychological anomalies are also acquired ample of importance in last few decades. Progressive research has showcased several obvious incidences of cognitive and psychological anomalies in the pathophysiology of PD. It has been reported that, almost 30% PD sufferers show different degree of cognitive impairment but lack of awareness or negligence makes it diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…All sectors of the textile processing industry are striving to increase their sustainability [13] and the wool sector is no exception [14][15][16][17][18]. Research into the scouring of raw wool (wool scouring) has included investigations into the effects of ultrasound [19], complexing agents [20], increasing the value of recovered wool grease [21], the colour of scoured wool and many other aspects [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…All sectors of the textile processing industry are striving to increase their sustainability [13] and the wool sector is no exception [14][15][16][17][18]. Research into the scouring of raw wool (wool scouring) has included investigations into the effects of ultrasound [19], complexing agents [20], increasing the value of recovered wool grease [21], the colour of scoured wool and many other aspects [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Study done by Chaudhary KR et al showed that sleep disturbances, cognitive impairment and bowel/bladder disturbances were frequent in PD. 2 Shulman and Colleagues reported that NMS complex is frequently unrecognised and/or neglected by healthcare professionals. 3 Another International survey showed that 62.5% of NMS in PD remain unknown to healthcare professionals because patients are either too embarrassed to reveal them or are unaware that these symptoms are linked to PD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current drug therapy aiming to improve dopaminergic signaling did not completely restore motor functions & is associated with other non-motor symptoms such as dyskinesia, anxiety, depression, fatigue, sleep disturbance, or sensory symptoms [46]. In Parkinson's disease, when the level of dopamine decreases, there is also the decrease in another neurotransmitter, acetylcholine since the motor function of the striatum is dependent on the equilibrium between dopamine and acetylcholine.…”
Section: Non-dopaminergic Signalingmentioning
confidence: 99%